INTEGRASI SOSIAL ANTARA MASYARAKAT PENDATANG DENGAN MASYARAKAT SETEMPAT DI DESA TRANS KECAMATAN SAHU TIMUR - Mais, Yehezkiel; Purwanto, Antonius (HOLISTIK, Journal Of Social and Culture, 2019)
In the life of society, it is reasonable and possible, as each individual has different interests and when the interests between one another individual or group interests collided with other groups then there was a conflict. The appearance of a conflict cannot be separated from the life of a society, because the conflict is a phenomenon that cannot be eliminated from social interaction. The conflict can only be controlled and minimized, so that conflicts do not arise until the life threatening society, nation and State. In this integration has always been the hope and is able to solve problems that arise due to social conflicts. Sahu Timur subdistrict of the arrival of the Homesteader and other settlers. Compound it includes religious and tribal culture. There are at least some villagers Trans spread across the Eastern subdistrict Sahu. In indirect villagers Trans also has cultural compound carried by each ethnic group. The arrangement of the compound as it was, the community is a condition susceptible to conflict, in the process of intermingling between the natives of West Halmahera Regency with the Homesteader and other entrants. Nevertheless, its people coexist and the integration process in district Eastern Sahu is going well although there are ripples of conflict but it does not interfere with the harmony of the community. Community Trans village saw that restricting factor also greatly affect the process of social integration of the latest quick, one of the factors restricting the process of social integration that is a difference of religion, tribe, ethnic differences, language, and different the opinion at the time of discussion and Expat communities are usually always bring their own culture even though different cultures where high places them right now, so in the circumstances such need to Act from Government or a good village apparatus for harmonious these different cultures so that there are no problems or conflicts because of such differences. Keywords: integration, compound, conflict